Treatment of Obsessive-Compulsive Disorder Resistant to Serotonin Reuptake Inhibitors – A Systematic Review - Hall, Sara Raquel Dias (2021)
Trabalho Final do Mestrado Integrado em Medicina apresentado à Faculdade de Medicina